Change in Dietary Patterns and Change in Waist Circumference and DXA Trunk Fat Among Postmenopausal Women. Issue 10 (22nd August 2016) - Cespedes Feliciano, Elizabeth M.; Tinker, Lesley; Manson, JoAnn E.; Allison, Matthew; Rohan, Thomas; Zaslavsky, Oleg; Waring, Molly E.; Asao, Keiko; Garcia, Lorena; Rosal, Milagros; Neuhouser, Marian L.
Abstract : Objective: To examine whether changes in diet quality predict changes in central adiposity among postmenopausal women. Methods: At baseline and 3‐year follow‐up, Women's Health Initiative Observational Study participants completed food frequency questionnaires, and waist circumference was measured (WC, n = 67, 175). In a subset, trunk fat was measured via dual‐energy X‐ray absorptiometry (DXA, n = 4, 254). Using multivariable linear regression, 3‐year changes in dietary patterns (Healthy Eating Index‐2010, Alternate Healthy Eating Index‐2010, Alternate Mediterranean Diet, and Dietary Approaches to Stop Hypertension) were examined as predictors of concurrent changes in WC and, secondarily, DXA. Results: Mean (SD) age and 3‐year changes in weight and WC were 63 (7) years, 0.52 (4.26) kg, and 0.94 (6.65) cm. A 10% increase in any dietary pattern score, representing improved diet quality, was associated with 0.07 to 0.43 cm smaller increase in WC over 3 years (all P < 0.05). After adjusting for weight change, associations attenuated to 0.02 to 0.10 cm but remained statistically significant for all patterns except Alternate Mediterranean Diet. Results were similar for DXA trunk fat. Conclusions: Three‐year improvements in diet quality are modestly protective against gain in WC and partially explained by lesser weight gain. Achieving and maintaining a healthful diet after menopause may protect against gains in central adiposity.